An Empirical Study on Green-HRM Recent Trends and Their Effects in the Workplace with Special Reference to Pune Educational Institutions - Dhiman, Lakshit (Journal of Advanced Research in HR and Organizational Management, 2022)
Another concept, known as GHRM, is gaining popularity all around the globe at the moment. It has different meanings to different people depending on who you ask. The significance of GHRM is not yet completely understood. It means increasing efforts to enhance energy capacity or decrease the pollution created by our homes, businesses, and general living preferences in general. The most standard reason for being environmentally generous is a desire to mitigate the potentially damaging impact that pollution and energy use may have on the surrounding environment. The developments in GHRM and their effects on educational institutions are the primary topics of discussion in this study. This research will be given further scope to make environmental friendliness consistent with current regulations.